UAV - Red Green Blue (RGB) Point Cloud (PC) from Nybygget, 2019-04-26 - Asa Research Station (Swedish University of Agricultural Sciences, 2021)
Point cloud generated from photos taken from an UAV platform using photo-stereography techniques. Nominal pixel size is 5 cm. The points contain a value for color, from RGB photos.
Asa Research Station (2021). UAV - Red Green Blue (RGB) Point Cloud (PC) from Nybygget, 2019-04-26 [Data set]. Swedish Infrastructure for Ecosystem Science (SITES). https://hdl.handle.net/11676.1/lDVE--uwiGZpZUI-UYtTN5am
Keywords: SITES Spectral; Calibration/Validation; Digital Elevation / Digital Surface Models; Ecosystem functions; Plant Phenology; Reflectance; Soil Science; Markvetenskap; Agriculture, Forestry and Fisheries; Jordbruk, skogsbruk och fiske; Agricultural Science; Jordbruksvetenskap; Ecology; Ekologi; Multidisciplinary Geosciences; Multidisciplinär geovetenskap; Environmental Sciences; Miljövetenskap; Climate Science; Klimatvetenskap